A registry study of relapsed or refractory multiple myeloma pre‐exposed to three or more prior therapies including a proteasome inhibitor, an immunomodulatory agent and CD38‐targeted monoclonal antibody therapy in England. Issue 3 (10th June 2021) - Elsada, Ahmed; Zalin‐Miller, Amy; Knott, Craig; Caravotas, Leonidas
Abstract: Some patients with multiple myeloma are receiving treatment in clinical practice in England after prior exposure to a proteasome inhibitor, an immunomodulatory agent, and an anti‐CD38 monoclonal antibody. We investigated the characteristics of these patients, their outcomes, and the salvage therapies they received using the national cancer registry for England and linked healthcare data. After a median follow‐up time of 6.4 months from T 0, median overall survival and time to next treatment were 8.2 and 5.3 months, respectively. This real‐world data provide useful clinical insight into a little‐studied patient population and highlight the poor outcomes in the UK setting.